Antioxidant and cytotoxicity activities of δ-tocotrienol from the seeds of Allophylus africanus. Issue 18 (8th September 2022) - Zeutsop, Jean Francois; Zébazé, Joviale Nouboudem; Nono, Raymond Ngansop; Frese, Marcel; Chouna, Jean Rodolphe; Lenta, Bruno Ndjakou; Nkeng-Efouet-Alango, Pépin; Sewald, Norbert
Abstract: Chemical investigation of Allophylus africanus P. Beauv fruits led to the isolation of a new δ -tocotrienol, 3 α -hydroxy-δ-tocotrienol (1 ) together with eight known compounds (2 -9 ). Compound (1) was allylated (1a ) and prenylated (1 b and 1c ) to give three new semi-synthesized derivatives which were fully characterized as: 6- O -allyl-3 α -hydroxy-δ-tocotrienol (1a ), 6- O -prenyl-3 α -hydroxy-δ-tocotrienol (1 b ) and 6- O, 5-C-diprenyl-3 α -hydroxy-δ-tocotrienol (1c ). The structures of compounds were established using comprehensive spectroscopic analysis including UV, MS, 1 D NMR, 2 D NMR and by comparison with the corresponding literature data. Compound (1 ) and its semi-synthetic derivatives (1a-c ) were tested for their antioxydant activity using DPPH radical scavenging assay and also for their cytotoxicity using human cervix carcinoma KB-3-1 cell lines. The results showed that compound (1) exhibited antioxidant activity with an IC50 value of 0.25 μ M compared to the reference control trolox (26 µ M); and good cytotoxic activity with IC50 values of 97 μ M compared to the reference (+)-griseofulvin (IC50 between17-21 μ M). Graphical Abstract: UF0001